Clinical Nurses’ Competence in Stroke Assessment: Knowledge, Practice, and Associated Factors in the Use of the National Institute of Health Stroke Scale - Yan, Tian; Laranang, Jonathan (Journal of Interdisciplinary Perspectives, 2026)
Stroke remains a leading cause of death and long-term disability worldwide, necessitating rapid and accurate assessment to improve patient outcomes. The National Institutes of Health Stroke Scale (NIHSS) is a standard tool for assessing neurological deficits in stroke patients. This study aimed to assess clinical nurses' knowledge and practice of the NIHSS and to analyze the relationships among sociodemographic characteristics, knowledge, and practice. A descriptive-correlational study design was conducted in September 2025 among 276 clinical nurses from Siping Central Hospital and Jilin Provincial Brain Hospital in China. A self-designed questionnaire was used to collect nurses' sociodemographic data, knowledge of the NIHSS, and practice. Results showed that clinical nurses had high knowledge and practice of the NIHSS. Educational background and number of training sessions were significantly correlated with knowledge, while years of service were significantly correlated with practice. Furthermore, knowledge and practice were significantly positively correlated, indicating that nurses with high knowledge were more adept at applying the NIHSS in clinical practice. These results emphasize the importance of ongoing education and systematic training to maintain nurses' competence in standardized stroke assessment.